2020
DOI: 10.20517/2347-9264.2020.77
|View full text |Cite
|
Sign up to set email alerts
|

Laser Resurfacing for the Management of Periorbital Scarring

Abstract: Laser (light amplification by the stimulated emission of radiation) skin resurfacing is currently one of the most widely adopted technologies in facial rejuvenation. While most often used for aesthetic purposes, lasers also have applications in the management of scars. Since the introduction of the CO 2 laser for skin rejuvenation in the 1990s, the last three decades have seen significant growth in the number of laser devices available to the physician. More recently, promising alternatives to light-based resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Only cold steel could ensure the kind of precision needed to treat tiny anatomical structures like microvessels, tiny muscles, and their aponeurosis without causing tissue distortions, functional impairments, or hemorrhages. It enables the surgeon to perform extremely delicate incisions and dissections 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only cold steel could ensure the kind of precision needed to treat tiny anatomical structures like microvessels, tiny muscles, and their aponeurosis without causing tissue distortions, functional impairments, or hemorrhages. It enables the surgeon to perform extremely delicate incisions and dissections 39 …”
Section: Discussionmentioning
confidence: 99%
“…It enables the surgeon to perform extremely delicate incisions and dissections. 39 The most significant benefit is the ability to heat tissue and enable perfect hemostasis in regions where the largest vessels have a diameter smaller than 1 mm when used in a defocused manner. 40 The use of a CO 2 laser during blepharoplasty has a wide range of beneficial effects, including an improvement in operating room efficiency, a shorter recovery period for patients than with scalpel surgery (which typically lasts 6−8 days longer), a reduction in bruising, and a shorter operating time (only 1 h for four eyelids blepharoplasty vs. 94 min for the scalpel manner).…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, many types of energy-based facial rejuvenation techniques have evolved including lasers, light-based devices, and non-light-based thermal tightening devices, and attempted for treatment of periorbital regions. 12,13 A study assessed the efficacies of treatment of periorbital regions using non-ablative fractional laser, non-ablative radiofrequency, and intense light source. 11 They showed that fractional non-ablative laser had the greatest impact on skin viscoelasticity as compared to other modalities.…”
Section: Discussionmentioning
confidence: 99%